Analisis Kinerja Dan Potensi Pertumbuhan Return Portofolio Reksadana Saham Dan Reksadana Campuran - Ferikawita M. Sembiring; Titianingsih Madjan Madjan (Universitas Airlangga, 2009)
The purposes of this study are to analyze the performance of the stock mutual funds and composite mutual funds in Indonesia and to analyze the potency of the return growth of those mutual funds. This study used the monthly return (net asset value-NAV) of 7 stock mutual funds and 11 composite mutual funds, from January 2002 to December 2006*. The monthly composite index of the JSX is used as the proxy for market return. Jensen model is used as the tool to measure of the performance (indicated by Jensen alpha) and the potency of the return growth (indicated by beta). To get an accuracy of the analysis and to avoid bias beta problem, this beta has to be corrected with Fowler and Rorke model, adopted from Capital Asset Pricing Model (CAPM). The main results of this research explained that the performance and the potency of the return growth of the stock mutual funds are higher than the composite mutual funds, during the period of analysis.